Phytochemical profiling, molecular docking, and ADMET evaluation of essential oils from Anaphalis busua and Anaphalis margaritacea in Uttarakhand's Himalayan Terrain - Ananya Bahuguna; Shiv Kumar Dubey; Arti (Elsevier, 2024)
Background: The study focuses on a comparative analysis of essential oils derived from two species of the Anaphalis genus, namely Anaphalis busua and Anaphalis margaritacea, collected at varying elevations in the hilly terrain of Uttarakhand. The investigation aims to explore the phytochemical composition, conduct in silico molecular docking studies, and evaluate ADMET properties of the essential oils to understand their potential bioactivity. Methods: Essential oils were extracted from the whole plants using the hydrodistillation method, and GC-MS was employed for compound identification. A total of 31 compounds were identified in A. busua and 32 in A. margaritacea, constituting 87.86 % and 87.83 % of the total composition, respectively. Major compounds included isocaryophyllene, caryophyllene oxide, geranyl-α-terpinene, α-pinene, γ-muurolene, δ-cadinene, humulene, and copaene. Results: Molecular docking studies were conducted using PyRx software on ten notable compounds as ligands, targeting cyclooxygenase-2 (COX-2) and human peroxiredoxin 5 to assess antioxidant and anti-inflammatory activities. Isocaryophyllene, with concentrations of 14.07 % (A. busua) and 17.82 % (A. margaritacea), exhibited significant binding affinities of -5.7 and -7.2 kcal/mol against 1HD2 and 4COX, respectively. Conclusion: The research provides valuable insights into the chemical composition of essential oils from Anaphalis plants and validates their bioactive potential through in silico analysis. Isocaryophyllene emerges as a key compound with noteworthy binding affinities, emphasizing its importance in the medicinal and pharmacological applications of essential oils derived from A. busua and A. margaritacea. The results enhance our understanding of the therapeutic potential of Anaphalis essential oils, opening avenues for future research in natural products and drug discovery.